Global perspectives on the state of resettlement practice in mining. Issue 1 (2nd January 2017) - Kemp, Deanna; Owen, John R.; Collins, Nina
Abstract: This article presents the results of a global study on resettlement practice in the mining industry. We examine how international policy commitments are operationalised by the mining sector and how practitioners from across the institutional spectrum engage with planning and implementation efforts by the industry. Interviews were conducted with 52 senior practitioners from mining companies, consultancies, international finance institutions and international non-government organisations. Results confirm knowledge, resourcing, capacity and coordination gaps among each of the institutions. These findings give additional substance to emerging reports about the urgent need to improve performance in this area of practice. The article concludes with a call for further sector-specific research into mining and resettlement.